To Study the Influence of Social Media Marketing of Branded Clothes on Purchase Intentions of Genz’s in Ahmedabad City - Meetkumar, Bhatt; Hetulkumar, Patel; Vidani, Jignesh (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
In recent times, social media has become crucial platform for clothing brands to sell and do marketing of their products, as brands use through it can engage with its audience through the features of social media platforms. For that reason, this study aims to find out how the social media marketing of branded clothes, like marketing through collaboration with influencers and sponsored advertisement done by clothing brands influence the purchasing intention of Generation Z. The place where we are doing the research is Ahmedabad, a city highly popular for its culture and its historical connection with clothes, so it's an ideal city to carry out the research on this subject. Through Google Forms, we have collected crucial data to measure the effect of social media marketing on Gen Z decision-making, while purchasing branded clothes. For that reason, by conducting this research, we are focusing to suggesting and offering some important insights to clothing brands about the importance of social media marketing and trying to help them in making efficient marketing strategies that can influence the purchase intention of Gen Z in Ahmedabad city